Performances of novel custom 3D-printed cutting guide in canine caudal maxillectomy: a cadaveric study - Chambers, Aidan; Traverson, Marine; Neal, Shelby; Konala, Satyanarayana; Harrysson, Ola (Frontiers in Veterinary Science, 2023)
Caudal maxillectomies are challenging procedures for most veterinary surgeons. Custom guides may allow the procedure to become more accessible. A cadaveric study was performed to evaluate the accuracy and efficiency of stereolithography guided (3D-printed) caudal maxillectomy. Mean absolute linear deviation from planned to performed cuts and mean procedure duration were compared pairwise between three study groups, with 10 cadaver head sides per group: 3D-printed guided caudal maxillectomy performed by an experienced surgeon (SG), a novice surgery resident (NG), and freehand procedure performed by an experienced surgeon (SF). Accuracy was systematically higher for SG versus SF, and statistically significant for 4 of 5 osteotomies (p<0.05). There was no statistical difference in accuracy between SG and NG. The highest absolute mean linear deviation for SG was <2 mm and >5 mm for SF. Procedure duration was statistically significantly longer for SG than SF (p<0.001), and for NG than SG (p<0.001). Surgical accuracy of canine caudal maxillectomy was improved with the use of our novel custom cutting guide, despite a longer duration procedure. Improved accuracy obtained with the use of the custom cutting guide could prove beneficial in achieving complete oncologic margins. The time increase might be acceptable if hemorrhage can be adequately controlled in vivo. Further development in custom guides may improve the overall efficacy of the procedure.